Efectos psicosociales de la Comisión de la Verdad en Brasil - Mathias, Anderson (2024)
A Truth Commission (TC) was carried out in Brazil (2012-2014) to investigate human rights violations perpetrated by state agents, especially during the military dictatorship (1964-1985). TCs are supposed to help societies on the reconstruction of social cohesion after authoritarian or violent periods. We conducted three studies with undergraduate students and adult samples between 2014 and 2017. Evaluating the TC as effective was related to higher punctuations on the variables of social cohesion, even controlling the effects of political positioning. The TC effectiveness perception was associated with the emotional reaction (both, negative or positive) and a positive attitude towards remembering the past. Nonetheless, we found some different results across the three studies. These differences are discussed.